A Systematic Literature Review on the Integration of Digital Technology in Islamic Religious Education at Secondary Schools - Amrulloh, Muhamad; Rajaminsah, Rajaminsah; Yudiyanto, Mohamad; Riyanti, Riyanti; Firdausi, Melisa Indah (PT. BATARI EDU CALYA, 2025)
This article offers an in-depth review of how digital technology is being incorporated into Islamic Religious Education (IRE) at secondary schools. The primary goal of the study is to evaluate the latest trends, challenges, and impacts of using digital tools in teaching IRE. By analyzing research from 2015 to 2024, the review aims to provide a comprehensive understanding of how digital technologies can enhance IRE and identify key factors for successful integration. The research was conducted using a library-based approach, examining relevant academic publications. The findings show that although digital technology holds the potential to improve the quality of IRE, various challenges need to be overcome. These challenges include limited access to digital resources, insufficient teacher training, and varying levels of digital literacy among both educators and students. Despite these hurdles, the results suggest that digital tools can significantly increase student engagement, create more interactive learning experiences, and allow for personalized learning. The study’s implications stress the need for specialized professional development programs for teachers, better access to digital resources, and the integration of digital literacy into the curriculum. To fully realize the potential benefits of digital technology in IRE, it is crucial for schools and policymakers to focus on these areas.